Decision making, some individual decision-making styles and software for decision making - Petrova Elitsa S.; Ştefănescu Roxana (2022)
This article presents the eternal relevance of the decision-making process and its inseparable connection with the personality of the decision-maker. Broadly speaking, the subject of consideration is the decision-making process. The main goal of the authors is to review the decision-making process, some styles of decision making and offer information about some types of software for decision making and strategic planning.